Highly reactive electrogenerated zinc: Preparation and its use in cross-coupling reactions - Aishah, Abdul Jalil; Sugeng, Triwahyono; Nobuhito, Kurono; Shingo, Takasugi; Masao, Tokuda (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/